Current Smoking Dose-Dependently Associated with Decreased β-Cell Function in Chinese Men without Diabetes. (5th July 2015) - Wang, Chun; Wang, Yijun; Wu, Junxia; Liu, Suyi; Zhu, Ying; Lv, Shurong; Lin, Ping; Wang, Xiaoke; Xu, Yan; Yu, Shali; Chen, Gang; Xiang, Quanyong
Abstract : The aim of this study was to evaluate the associations between chronic smoking and insulin resistance and β -cell function in Chinese men without diabetes. A total of 1, 568 participants were recruited by multistage sampling. Using homeostatic model assessment (HOMA), geometric means of insulin resistance (HOMA-IR) and β -cell function (HOMA- β ) with 95% confidence interval (CI) were calculated by general linear model. Odds ratios (ORs) with 95% CI were estimated to evaluate the associations between smoking status and insulin resistance and β -cell deficiency under a logistic regression model. Current smokers had higher levels of 2 h glucose (6.66 versus 6.48 mmol/L) for oral glucose tolerance test and lower levels of fasting insulin (5.68 versus 6.03 mU/L) than never smokers. The adjusted means for HOMA- β (%) were 54.86 in current smokers and 58.81 in never smokers (P = 0.0257 ). Current smoking was associated with β -cell deficiency (OR 1.29, 95% CI 1.01–1.64) compared to never smoking. The β -cell function gradually decreased with increasing smoking intensity (P trend = 0.0026 ), and the differences were statistically significant when the pack-year of smoking was 20 or above. No association was observed between smoking status and HOMA-IR. Our study suggested that chronic smoking may dose-dependently suppress insulin secretion in Chinese men.